Effectiveness of verbal, verbal-written and video instructions on gingival health of patients with fixed appliances - Cheong, Joo Ming; M. Ashaari, Norul Madihah; Mohamad Yusoff, Razan Hayani; Tolos, Siti Marponga (SciDoc Publishers, 2022)
Background: Orthodontic treatment causes detrimental effects on periodontal health due to the accumulation of dental plaque. This problem can be prevented by implementing effective oral hygiene instructions (OHI).